If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 17 + 3x + -11 = 0 Reorder the terms: 17 + -11 + 3x = 0 Combine like terms: 17 + -11 = 6 6 + 3x = 0 Solving 6 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 0 + -6 3x = 0 + -6 Combine like terms: 0 + -6 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2

| X-20=-7 | | 5x-8=32 | | 6+x=23 | | 10(5x-3)=20 | | 25-9= | | 8=14+x | | 7(2x-4)=28 | | 3=-6+x | | 42j+18-19j=28 | | 25=9+9(8xf) | | 13x-(x+7)=29 | | 25=9+(8xf) | | 3(2r+1)=6(r+2)-6 | | 25=9+(8f) | | 4(7x+6)=80 | | 49=1+6x | | 15=8x-1 | | -5+18a=-77 | | x-.625=.875 | | -15=5(39-10)-59 | | -2(x+3)=4x-3 | | 4x-5(3x+10)=126 | | 5+x=23 | | 2+x=13 | | P=2 | | (7y-34)=5y | | X-27=-25 | | 7x-2(3+4x)=19 | | 12=3.1y-59.3 | | 10=d-120 | | 3+x=9 | | (18y-18)=16y | | 14=11x+3 | | 4=x-12 | | 15+3(2x-9)=60 | | 3=x-1 | | 28-6(2x+4)=124 | | 7+x=5 | | 3(2x+1)+5=14 | | -40=4(x-10) | | 12=x+11 | | 20=-5(x+7) | | -6(2x+3)=42 | | 30=10+(5x) | | -2(x+7)=16 | | 5x-10x+2=-3x+6 | | 3(2x+3)=9(x-3) | | 7(x+4)=9(x-2) | | 1+1=2 | | 5+x+3=14 | | 2(10+x)+4(12-x)=34 | | 4x+9x+1=27 | | 4(x+7)=16 | | 18-2(x-3)=26 | | x-1=2x-15 | | x-1=-2x-15 | | 12r-4r=4 | | 12r-4r-4=4 | | 8(4x+8)+(x+2)=11 | | 10=12-h | | 11b-9b=18 | | 11(x-6)-17=38 | | 4x+5(x-5)=4(x-5) | | 2p-2(3-2p)=2(p-6)-14 | | 4x+6y=20 |